Stereotipe Masyarakat Terhadap Kemampuan Tunanetra - Mulyani, Hani; Zharfan, Faza Zahra; Ikbal, Muhamad Nasrul; Yani, Nur Afifah April; Hamidah, Siti (STAI Denpasar Bali, 2023)
A This study discusses society's stereotypes about the ability of the blind.The stereotypes in question are general views and negative prejudices against the abilities and independence of the blind, so as to reduce their chances of being prioritized for facilities and not getting the opportunity to be empowered.The purpose of this study is to understand the factors that influence stereotypes about the ability of the blind and provide recommendations to reduce these stereotypes.The research method used is an online survey of respondents who are members of the general public from various backgrounds.The results of this study indicate that society's stereotypes regarding the ability of the blind are still very strong and are driven by internal and external factors of the blind themselves, such as social factors, lack of public knowledge about the ability of the blind, as well as self - faith that arises from the blind themselves.Not surprisingly, there are still many who think that blind people are less powerful when compared to sighted people.Therefore, efforts need to increase public awareness and knowledge about the abilities of the blind and eliminate existing stereotypes.